Physicochemical characterization, antioxidant activity and total phenolic content in 'Gala' apples subjected to different UV-C radiation doses - Dias, Thaís Gabrielle (2017)
UV-C radiation is a food preservation method aimed to extend the life of the product, inactivate microorganisms, and stimulate the synthesis of phenolic compounds. This study aimed to physicochemically characterize and evaluate the antioxidant activity and phenolic content of ‘Gala’ apples subjected to different UV-C radiation doses.The fruits were harvested, sanitized, selected and inserted into a UV-C radiation chamber, and different radiation doses were applied as follows:0 KJ m-2 (0 min.), 0.68 KJ m-2 (2 minutes),2.73 KJ m-2 (4 minutes), and 4.10 KJ m-2 (6 minutes). The apples were stored for 120 days at 5 ± 1°C and analyzed after 0, 30, 60, 90, and 120 days of storage. Radiation doses had no influence on parameters, such as weight loss, firmness and Hue angle, and physicochemical aspects, such as pH, soluble solids, titratable acidity and the soluble solids/titratable acidity ratio. The 4.10 KJ m-2 dose was effective and increased the phenolic content and antioxidant activity for up to 90 days while maintaining the content of vitamin C during storage.